An opportunist predator hidden in the vegetation: on the predation of birds by Philodryas olfersii (Serpentes: Dipsadidae) - Mise, Fabio Teruo; Deliberador Miranda, Joao Marcelo; Santos, Danusy Lopes [UNESP]; Curcino, Alexandre; Oda, Fabricio Hiroiuki (Taylor & Francis Ltd, 2021)
Snakes are common predators of birds. However, reported cases of snake predation on Troglodytes musculus are scarce. Here, we report a predation attempt of a Troglodytes musculus nestling by the dipsadid snake Philodryas olfersii. We also present a list with bird species recorded as prey of this snake species. We found 25 predation events of P. olfersii on adult, juvenile, and nestling birds. A total of 19 bird species from 14 families have been reported as prey of P. olfersii. Most predation events occurred on the vegetation, while some others were observed on the ground, cage, and artificial nest.
Keywords: Dipsadidae; green snake; nestling predation; Troglodytidae